Bank lending policies : issues and practices - Hayes, Douglas Anderson (Ann Arbor, Mich. : Bureau of Business Research, Graduate School of Business Administration, University of Michigan, 1964)
The purpose of this book is to present an analysis of the issues involved in the formulation and execution of bank lending policies.
Bibliographical footnotes.
ne 23/09/2019
Loans
Keywords: Bank loans